Dynamic template for lecturers' webpages in FTMSK / Wan Ahmad Muzzammil Ariff Wan Mohd Mahidin - Wan Mohd Mahidin, Wan Ahmad Muzzammil Ariff (2003)
Most universities today have the problem of administrating the personal web pages of their lecturers on their campus servers. This problem usually leads to an inconsistent range of web page styles that may or may not fulfill the purpose of a lecturer's web page. This project is done to overcome this problem by providing a way for the lecturers to create and maintain their web page by using a dynamic template. Thus, the web pages will adhere to a specified guideline and be more productive. Initially, a research must be done through a quantitative survey to collect requirements from the lecturers, where the lecturers will be asked for their opinions on what should exist on their web pages. The analysis of the results would serve as a tool in creating a guideline to create the dynamic template for the lecturers' web pages. This project was conducted using open source technology, which include the Apache web server, PHP scripting language, and the MySQL relational database management system.